Miriam Chaszczewacka’s Diary - Tych, Feliks (Zagłada Żydów. Studia i Materiały, 2013)
Diary of Miriam Chaszczewacka, a teenage resident of Radom. She wrote it since August 1939 – she started on the eve of the Third Reich’s attack on Poland – until the end of October 1942, when she was killed during the liquidation of the ghetto. Written in Polish, conceived as a letter to the future generations, Miriam’s diary shows the daily life in the ghetto and the extermination of its population based on the example of Radom. Her diary entries are mostly spontaneous notes of a young girl writing about her life. But she also describes the deteriorating conditions of the life in the ghetto and the general political situation. Thisis a dramatic record of the increasing awareness of the inevitably approaching death.